Lussazione sotto-astragalica: una lesione rara - davini, P.G.; Simeone, A.J.V.; Biancalani, D.; Angelini, S. (Lo Scalpello - Journal, 2018)
SUBTALAR DISLOCATION: AN UNCOMMON INJURY Subtalar dislocation is defined as simultaneus dislocation of the subtalar and talonavicular joints. This orthopedic condition represents between 1% and 2% of all dislocations and, 15% of all peritalar injuries. They occur more frequently in men in their mid-30 s. The rarity of subtalar dislocation is correlated to the strong ligaments and to the biomechanical properties of subtalar joint. Excellent results are generally obtained after treating dislocations without associated injuries.